A low warpage carbon fiber reinforced polyamide composite for robot structural parts and a method for manufacturing the same

By using low-warpage carbon fiber reinforced polyamide composite materials, the problems of heavy weight and warpage deformation in robot structural components have been solved, achieving lightweight, high strength and dimensional stability, which is suitable for high precision and long-term service reliability of robot structural components.

CN123042518APending Publication Date: 2026-11-06QINGDAO ZHONGBAO PLASTIC IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611297786.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing materials for robot structural components, such as aluminum alloys and glass fiber reinforced nylon, suffer from problems such as high weight, complex processing, and severe warping and deformation, making it difficult to meet the requirements of lightweight and high-precision assembly.

Method used

Low-warp carbon fiber reinforced polyamide composite material is used. By combining polyamide resin, carbon fiber, hollow glass microspheres, silane coupling agent, polyethylene grafted maleic anhydride and antioxidant, the interfacial bonding force and molding shrinkage are improved, and the warping deformation is reduced.

Benefits of technology

It achieves lightweight, high strength and dimensional stability of materials, adapts to the high precision and long-term service reliability of robot structural components, reduces warpage deformation, and improves wear resistance and antistatic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the technical field of polymer composites, and specifically discloses a low-warp carbon fiber reinforced polyamide composite material for robot structural parts and a preparation method thereof.The low-warp carbon fiber reinforced polyamide composite material for robot structural parts comprises the following raw materials: 60-70 parts of polyamide resin, 20-30 parts of carbon fiber, 0.6-0.9 parts of a silane coupling agent, 10-12 parts of hollow glass microbeads, 2-5 parts of polyethylene grafted maleic anhydride, and 0.5-0.8 parts of antioxidant 1010.The various components are matched, the high-strength characteristics of the carbon fiber and the low-shrinkage and low-warp of the hollow microbeads are taken into account, and the low-warp carbon fiber reinforced polyamide composite material is suitable for precise robot structural parts such as mechanical arm supports, connecting flanges and module housings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of polymer composite materials, and in particular to a low-warpage carbon fiber reinforced polyamide composite material for robot structural components and its preparation method. Background Technology

[0002] With the rapid development of intelligent industrial robots and collaborative robots towards lightweight, high precision, and high durability, core structural components such as robot arms, joint housings, connecting brackets, and transmission bases face stringent comprehensive requirements regarding the mechanical strength, dimensional stability, lightweight level, and forming and processing performance of materials. Currently, the mainstream materials for manufacturing robot structural components on the market are aluminum alloys and glass fiber reinforced materials. However, both types of materials have inherent technical defects that are difficult to avoid, which seriously restrict the assembly accuracy and service performance of high-end precision robot structural components.

[0003] Existing robotic arms, joint housings, and other structural components would be heavy and complex to manufacture if made of aluminum alloy. As the integration of robot joints continues to increase, the requirements for the degree of integration of structural components are also becoming more stringent, posing a growing challenge to traditional metal processing techniques in manufacturing complex integrated structural components. If glass fiber reinforced nylon is used, the significant anisotropy of molding shrinkage leads to severe warping and deformation of the product, failing to meet the dimensional stability requirements of high-precision assembly.

[0004] In summary, there is an urgent need to develop a reinforced polyamide composite material that is lightweight, high-strength, and has extremely low warpage to replace the traditional aluminum alloy and glass fiber reinforced nylon in the structural components of robot arms, joint housings, etc., so as to achieve structural lightweighting while ensuring the dimensional accuracy and long-term service reliability of the products. Summary of the Invention

[0005] In order to improve the problems of low strength and severe warping deformation of traditional materials in the prior art, this application provides a low-warping carbon fiber reinforced polyamide composite material for robot structural parts and its preparation method.

[0006] This application provides a low-warpage carbon fiber reinforced polyamide composite material for robot structural components, employing the following technical solution: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components comprises, by weight, the following raw materials: 60-70 parts polyamide resin, 20-30 parts carbon fiber, 0.6-0.9 parts silane coupling agent, 10-12 parts hollow glass microspheres, 2-5 parts polyethylene grafted maleic anhydride, and 0.5-0.8 parts antioxidant 1010.

[0007] By adopting the above technical solutions, polyamide resin exhibits high mechanical strength, fatigue resistance, wear resistance, resistance to lubricating oil / cleaning agents, and high heat distortion temperature, meeting the load-bearing and durability requirements of robot arms, mounting supports, and transmission housings. Carbon fiber enhances tensile, flexural, and compressive strength and modulus, reduces the material's coefficient of linear expansion, and ensures structural dimensional stability under high-speed reciprocating motion of the robot. The silane coupling agent hydrolyzes and bonds alkoxy groups at one end to the inorganic surface of carbon fiber and glass microspheres, while the amino / epoxy groups at the other end form hydrogen bonds and covalent bonds with PA molecular chains, improving the wetting and dispersion effect of inorganic fillers in the PA matrix. This reduces filler agglomeration, weakens filler-resin interface defects, reduces interface stress concentration, and minimizes warping factors at the microscopic level.

[0008] Hollow glass microspheres can significantly reduce material density, while their isotropic spherical structure helps reduce anisotropic shrinkage during molding, thereby suppressing warpage; improving dimensional stability, reducing post-molding creep, and preventing dimensional deviation under long-term robot load. Polyethylene grafted with maleic anhydride undergoes an amidation reaction with the amino groups at the PA terminals, resulting in physical entanglement between polyethylene segments, carbon fiber surfaces, and hollow glass microspheres, further strengthening interfacial bonding. The hollow glass microspheres, in conjunction with the polyethylene grafted with maleic anhydride, synergistically regulate the overall molding shrinkage rate. The flexible PE segments buffer the internal stress during curing and cooling, releasing residual injection stress and significantly reducing warpage deformation in uneven thickness and long, narrow robot structural components.

[0009] Antioxidant 1010 inhibits the thermal oxidative degradation of PA molecules, carbon fiber surface oxidation, and thermal decomposition of polyethylene grafted maleic anhydride, preventing the material's mechanical strength from decreasing, products from becoming brittle and cracking, and extending the service life of structural components. Carbon fiber provides high strength and rigidity to meet structural load-bearing requirements, while hollow glass microspheres counteract crystallization shrinkage and improve the anisotropy of carbon fiber orientation, solving the inherent warping problem. Silane coupling agents and polyethylene grafted maleic anhydride double-layer interface modification ensure uniform dispersion of inorganic fillers, eliminating interface porosity and local stress concentration. The flexible phase of polyethylene grafted maleic anhydride releases residual internal stress from injection molding, further suppressing rebound warping after demolding. Combining the high strength of carbon fiber with the low shrinkage and low warping of hollow microspheres, it is suitable for precision robot structural components such as robotic arm supports, connecting flanges, and module shells.

[0010] Preferably, the polyamide resin is treated with fluorite and nano-titanium dioxide.

[0011] By adopting the above technical solution, polyamide resin, after modification and pretreatment, serves as a modified base material for carbon fiber / hollow glass microsphere reinforced PA composites. Pre-modification can improve the crystallization behavior, melt processing fluidity, surface polarity, heat resistance, and wear resistance of pure PA, laying the foundation for subsequent filling with carbon fibers and hollow microspheres. Fluorite acts as a heterogeneous nucleating agent, refining the size of PA spherulites, making the crystal arrangement more uniform, and reducing uneven shrinkage during PA crystallization. Combined with the formulation, it further achieves the low warpage characteristics of the overall composite material. Coarse spherulites are prone to causing high internal stress and product deformation; refining the grains can release internal stress.

[0012] Fluorite, with its moderate hardness and excellent solid lubrication properties, can be embedded within the PA matrix to reduce the coefficient of friction in structural components, thereby minimizing wear and noise in moving robot parts and extending their lifespan. Nano-titanium dioxide possesses UV shielding capabilities, absorbing and scattering ultraviolet light to inhibit molecular chain breakage and aging in PA under long-term light exposure and UV disinfection environments, thus improving the long-term dimensional stability of exposed robot components. Nanoscale particles fill the gaps between PA molecular chains, slightly increasing the rigidity and hardness of the substrate; simultaneously, these nanoparticles optimize the surface activity of the matrix, resulting in tighter bonding with subsequent silane-modified carbon fibers and hollow glass microspheres, reducing interface defects.

[0013] First, modified PA matrix granules are prepared, and then the modified PA is used to replace the original pure PA resin. It is then combined with carbon fiber, hollow glass microspheres, silane coupling agent, polyethylene grafted maleic anhydride, and antioxidant 1010 for secondary blending, extrusion, and granulation. This results in improved anti-aging and wear resistance, better filler dispersion, and ultimately, a composite material with lower warpage, better wear and weather resistance, and a wider processing window, making it more suitable for high-precision robot structural parts.

[0014] Preferably, the carbon fiber is treated with talc and epoxy resin emulsion.

[0015] By adopting the above technical solution, epoxy resin is continuously filmed and firmly anchored on the inert surface of carbon fiber. The epoxy groups react chemically with the terminal amino groups of polyamide molecules and the anhydride groups of PE-g-MAH to form chemical bond interface bonding, which greatly improves the interfacial bonding strength between carbon fiber and PA matrix, enhances the mechanical strength and interlaminar strength of composite material, and reduces interfacial debonding defects.

[0016] Talc reduces the shrinkage difference between carbon fiber and PA matrix, alleviates anisotropic shrinkage caused by carbon fiber orientation, reduces warpage of robot structural components, imparts solid lubrication effect to the surface of carbon fiber, reduces fiber entanglement and screw wear during extrusion processing, improves overall filler dispersion, enhances wear resistance of composite materials, and adapts to reciprocating friction conditions of robot moving structural components.

[0017] This modified carbon fiber addresses the two major pain points of weak interfacial bonding and easy agglomeration of virgin carbon fiber, ensuring the high strength of the composite material. The bidirectional synergistic regulation of shrinkage rate by the encapsulated talc powder and hollow glass microspheres in the matrix is ​​the key design to achieve low warpage. The HEC flexible component releases interfacial stress, and together with the previously modified fluorite PA substrate and modified carbon black masterbatch, it simultaneously achieves multiple properties such as high strength, dimensional stability, antistatic properties, and weather and wear resistance.

[0018] Preferably, the epoxy resin emulsion is mixed with dried talc powder, deionized water is added, and the mixture is stirred evenly to obtain a mixture; the chopped carbon fibers are immersed in the mixture, centrifuged, spread out and dried to obtain treated carbon fibers.

[0019] By adopting the above technical solution, the epoxy resin is firmly attached to the surface of carbon fiber after curing. The epoxy groups can react chemically with the amino groups of PA molecular chain and the anhydride groups of PE-g-MAH to form a strong chemical bonding interface, which greatly improves the interfacial bonding strength between carbon fiber and polyamide matrix, and enhances the tensile, flexural strength and interlayer bonding force of composite materials.

[0020] Talc powder adheres to the surface of carbon fiber along with the resin film, filling the gaps during matrix molding, balancing resin curing shrinkage, reducing the anisotropic shrinkage differences caused by carbon fiber orientation, and further optimizing the product warpage problem; a thin layer of talc powder is coated on the surface of carbon fiber, reducing fiber entanglement and agglomeration during extrusion granulation, reducing fiber wear on the equipment screw, and improving the smoothness of material extrusion.

[0021] The PA matrix is ​​pre-modified with fluorite and nano-TiO2 to optimize its crystallization and processing properties; carbon fiber is used for epoxy composite coating modification to strengthen the interfacial bonding force, and talc is used to control the interfacial shrinkage stress; hollow glass microspheres are used to balance the overall shrinkage rate, PE-g-MAH is used for secondary compatibilization, and silane coupling agent is used for auxiliary modification; the interfacial bonding force is high, the filler is evenly dispersed, the shrinkage is consistent throughout, and the internal stress is low, which perfectly matches the high strength, high precision, low warpage, wear resistance, antistatic properties, and aging resistance of robot structural components.

[0022] Preferably, the hollow glass microspheres are treated with graphene and silane coupling agent KH-550.

[0023] By adopting the above technical solution, silane alkoxy groups are hydrolyzed in an ethanol-water system to generate silanol, which undergoes dehydration condensation with the silanol on the surface of the hollow glass microspheres to generate stable Si-O-Si covalent bonds, which are firmly anchored on the surface of the microspheres; the terminal amino groups can chemically react with the PA matrix, PE-g-MAH, and epoxy coating layer on the carbon fiber surface to eliminate interfacial gaps and interfacial debonding defects between inorganic microspheres and organic resin.

[0024] The primary function of hollow glass microspheres is weight reduction, balanced shrinkage, and reduced warpage; however, filling them slightly reduces material strength and toughness. The coated sheet graphene can create a microscopic reinforcing network around the microspheres, offsetting the mechanical degradation caused by the hollow structure, achieving a balance between low warpage and lightweight design and structural strength, making it suitable for robot load-bearing structural components. The graphene attached to the microsphere surface acts as heterogeneous nucleation sites, refining the size of polyamide spherulites, resulting in more uniform and regular resin crystallization, reducing internal residual stress caused by uneven crystallization shrinkage, and synergistically suppressing anisotropic deformation in the flow direction / perpendicular direction of injection-molded parts. Graphene possesses excellent sheet lubrication effects, reducing the coefficient of friction of composite materials and improving the mechanical properties, wear resistance, and durability of robot moving components.

[0025] Preferably, graphene is dispersed in a mixture of ethanol / deionized water, silane coupling agent KH-550 is added, and the mixture is stirred for 15-20 minutes to obtain the mixture. Hollow glass microspheres were immersed in a mixed solution, centrifuged, and dried to obtain pretreated hollow glass microspheres.

[0026] By employing the above technical solution, KH-550 alkoxy groups are hydrolyzed to generate silanol. The silanol undergoes dehydration condensation with the silanol on the outer wall of the hollow glass microspheres, forming a stable Si-O-Si covalent bond that is firmly grafted onto the surface of the microspheres. The amino group at the other end of the molecule can chemically react with the amide bond of the PA matrix, the PE-g-MAH anhydride group, and the epoxy coating on the carbon fiber surface, greatly improving the interfacial bonding strength between the hollow glass microspheres and the polyamide matrix, eliminating interfacial gaps and debonding problems. Hollow glass microspheres can reduce weight, shrinkage, and warp, but excessive addition will cause a decrease in the strength and toughness of the composite material. After coating with graphene, the sheet graphene builds a local reinforcing network, compensating for the mechanical losses caused by the hollow structure, achieving low warp and lightweight while ensuring the mechanical load-bearing performance of the robot structural components.

[0027] Graphene attached to the surface of the microspheres acts as heterogeneous nucleation sites, regulating the crystalline morphology of PA, reducing the size of crystalline regions, and lowering the internal stress caused by uneven crystallization. Combined with the bidirectional counteracting of anisotropic shrinkage caused by carbon fiber orientation by the spherical hollow microspheres, this further enhances the material's low warpage characteristics. Graphene also possesses solid lubricating properties, reducing the coefficient of friction in the reciprocating motion of structural components and improving wear resistance, mechanical properties, and service life.

[0028] Fluorite and nano-TiO2 modified PA resin optimize matrix crystallinity, weather resistance, and processability; epoxy-HEC-talc modified short-cut carbon fiber ensures high strength modulus of the main body; graphene / KH550 modified hollow glass microspheres balance weight reduction, shrinkage balance, stress relief, reinforcement, and antistatic properties; the entire system features multi-layer interface modification and matching, resulting in strong interface bonding, uniform filler dispersion, and low internal stress, perfectly meeting the full requirements of high strength, low warpage, lightweight, wear resistance, antistatic properties, and aging resistance for precision structural components of industrial robots.

[0029] Secondly, this application also provides a method for preparing low-warpage carbon fiber reinforced polyamide composite materials for robot structural components, comprising the following steps: Polyamide resin, silane coupling agent, hollow glass microspheres, polyethylene grafted maleic anhydride, and antioxidant 1010 are mixed evenly to obtain a mixed raw material. The above mixed raw material and carbon fiber are placed in the main feed port and side feed port of a twin-screw extruder, respectively, and then melt-extruded and granulated to obtain a low-warpage carbon fiber reinforced polyamide composite material for robot structural parts.

[0030] By adopting the above technical solution, the integrity of the hollow glass microsphere shell is protected and the length of the carbon fiber is preserved; the interface modification is completed in stages, the inorganic microspheres first fully react with silane and matrix, and the carbon fiber is then mixed in and interface bonding is achieved with the help of compatibilizer. The filler is more uniformly dispersed, the internal residual stress of the composite material is lower, and the difference in shrinkage between the flow direction and the vertical direction of injection molding is effectively suppressed, achieving the core goal of low warpage, while taking into account the mechanical strength and dimensional stability of the material, and meeting the requirements of the precision structural parts of robots.

[0031] Preferably, the twin-screw extruder is configured as follows: zone 1 temperature 240-250℃, zone 2 temperature 250-260℃, zone 3 temperature 250-260℃, zone 4 temperature 260-270℃, zone 5 temperature 270-280℃, zone 6 temperature 260-270℃, zone 7 temperature 250-260℃, and screw speed 320-330 rpm / min.

[0032] By adopting the above technical solution, the temperature gradient rises and falls smoothly, matching the temperature tolerance of the organic coating film on the outer layer of the modified filler, preserving the modification effect of the filler, and reducing the warpage of the composite material from the interface source; all components are fully melted and compatible, and the filler is uniformly dispersed, ensuring that the mechanical strength, dimensional stability, wear resistance and antistatic properties of the product are stable and meet the standards; the thermal environment is controllable throughout the process, and with the addition of antioxidant 1010, the processing thermal aging is effectively suppressed, and the finished particles have normal color and small performance fluctuations, making them suitable for injection molding of precision structural parts for robots.

[0033] In summary, this application has the following beneficial effects: 1. The hollow glass microspheres in this application can significantly reduce the material density, and their isotropic spherical structure helps to reduce the anisotropic shrinkage of the material during molding, thereby suppressing warping; improving dimensional stability, reducing creep after molding, and making the dimensions less prone to deviation under long-term robot load.

[0034] 2. The multi-component combination in this application takes into account the high strength of carbon fiber and the low shrinkage and low warpage of hollow microspheres, making it suitable for precision robot structural components such as robotic arm brackets, connecting flanges, and module shells.

[0035] 3. In this application, carbon fiber improves tensile, bending, and compressive strength and modulus, reduces the coefficient of linear expansion of the material, and ensures the structural dimensional stability under the high-speed reciprocating motion of the robot. Detailed Implementation

[0036] The present application will be further described in detail below with reference to the embodiments.

[0037] The raw materials used in the examples and comparative examples are all commercially available.

[0038] Preparation Example 1 The polyamide resin is treated with polyamide resin, fluorite, and nano titanium dioxide.

[0039] 80 kg of polyamide resin, 15 kg of fluorite, 4 kg of nano titanium dioxide, and 1 kg of calcium stearate were mixed, melt-extruded and granulated at 260°C to obtain the treated polyamide resin; the fluorite powder was purchased from Shijiazhuang Taikuang Mineral Products Co., Ltd.

[0040] Preparation Example 2 The difference from Preparation Example 1 is that fluorite is not added during the polyamide resin treatment.

[0041] Preparation Example 3 The difference from Preparation Example 1 is that no nano-titanium dioxide is added during the polyamide resin treatment.

[0042] Preparation Example 4 Carbon fiber is treated with talc and epoxy resin emulsion.

[0043] 8 kg of epoxy resin emulsion (purchased from Jining Juji New Materials Co., Ltd.) was mixed with 13 kg of dried talc powder, and 20 kg of deionized water was added. The mixture was stirred evenly to obtain a solution. 30 kg of chopped carbon fibers were immersed in the solution, centrifuged, spread out and dried to obtain treated carbon fibers.

[0044] Preparation Example 5 The difference from Preparation Example 4 is that no talc is added during the carbon fiber processing.

[0045] Preparation Example 6 The difference from Preparation Example 4 is that no epoxy resin emulsion is added during the carbon fiber treatment process.

[0046] Preparation Example 7 Hollow glass microspheres are treated with graphene and silane coupling agent KH-550.

[0047] 1 kg of graphene was dispersed in a 60 L mixture of ethanol and deionized water (ethanol:deionized water = 7:3), 0.08 kg of silane coupling agent KH-550 was added, and the mixture was stirred for 20 min to obtain the mixture. 12 kg of hollow glass microspheres were immersed in the mixed solution, centrifuged (300 rpm for 2 min), and dried to obtain pretreated hollow glass microspheres.

[0048] Preparation Example 8 The difference from Preparation Example 7 is that no graphene is added during the hollow glass microsphere processing.

[0049] Preparation Example 9 The difference from Preparation Example 7 is that no silane coupling agent KH-550 is added during the hollow glass microsphere treatment.

[0050] Example 1 A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, comprising the following raw materials by weight: 70 kg of polyamide resin, 20 kg of carbon fiber, 0.9 kg of silane coupling agent KH560, 10 kg of hollow glass microspheres, 2 kg of polyethylene grafted maleic anhydride, and 0.8 kg of antioxidant 1010.

[0051] The polyamide resin was purchased from Shanghai Liu Zhangyang Plastics Co., Ltd.; the polyethylene grafted with maleic anhydride was purchased from Dongguan Shengli New Materials Co., Ltd.

[0052] The preparation method of the above-mentioned low-warpage carbon fiber reinforced polyamide composite material for robot structural components includes the following steps: mixing polyamide resin, silane coupling agent, hollow glass microspheres, polyethylene grafted maleic anhydride, and antioxidant 1010 evenly to obtain a mixed raw material; placing the above mixed raw material and carbon fiber into the main feed port and side feed port of a twin-screw extruder, respectively; performing melt extrusion and granulation to obtain the low-warpage carbon fiber reinforced polyamide composite material for robot structural components.

[0053] The settings for the twin-screw extruder are as follows: Zone 1 temperature 250℃, Zone 2 temperature 260℃, Zone 3 temperature 260℃, Zone 4 temperature 270℃, Zone 5 temperature 280℃, Zone 6 temperature 270℃, Zone 7 temperature 260℃, and screw speed 330 rpm / min.

[0054] Example 2: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 1 in that, by weight, it includes the following raw materials: 60 kg of polyamide resin, 30 kg of carbon fiber, 0.6 kg of silane coupling agent KH560, 12 kg of hollow glass microspheres, 5 kg of polyethylene grafted maleic anhydride, and 0.5 kg of antioxidant 1010.

[0055] The settings for the twin-screw extruder are as follows: Zone 1 temperature 240℃, Zone 2 temperature 250℃, Zone 3 temperature 250℃, Zone 4 temperature 260℃, Zone 5 temperature 270℃, Zone 6 temperature 260℃, Zone 7 temperature 250℃, and screw speed 320 rpm / min.

[0056] Example 3: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 1 in that the polyamide resin is prepared in Preparation Example 1.

[0057] Example 4: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 1 in that the polyamide resin is prepared by Preparation Example 2.

[0058] Example 5: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 1 in that the polyamide resin is prepared by Preparation Example 3.

[0059] Example 6: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 3 in that the carbon fiber is prepared by Preparation Example 4.

[0060] Example 7: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 3 in that the carbon fiber is prepared by Preparation Example 5.

[0061] Example 8: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 3 in that the carbon fiber is prepared by Preparation Example 6.

[0062] Example 9: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 6 in that the hollow glass microspheres are prepared using Preparation Example 7.

[0063] Example 10: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 6 in that the hollow glass microspheres are prepared using Preparation Example 8.

[0064] Example 11: A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, which differs from Example 6 in that the hollow glass microspheres are prepared using Preparation Example 9.

[0065] Comparative Example 1 A low-warpage carbon fiber reinforced polyamide composite material for robot structural components differs from Example 1 in that it does not contain hollow glass microspheres.

[0066] The performance of a robot structural component prepared in Examples 1-11 and Comparative Example 1 using a low-warpage carbon fiber reinforced polyamide composite material was tested. Tensile strength: Tested according to GB / T 1040.2-2022 standard.

[0067] Warpage: The test object is a square plate with injection molded dimensions of 60mm×6mm×1mm. Warpage (%) = maximum warpage height of the square plate / side length × 100%.

[0068] The notched impact strength of the cantilever beam is determined according to ASTM D256.

[0069] All test specimens were prepared by injection molding machine and tested after being conditioned for 48 hours in a standard environment of 50±5% relative humidity and 23±2℃. The test results are shown in Table 1.

[0070] Table 1 Test data for the examples and comparative examples

[0071] As shown in Table 1, the low-warpage carbon fiber reinforced polyamide composite materials for robot structural components prepared in Examples 1-2 of this application exhibit good mechanical properties and low warpage. Specifically, Example 1 shows a tensile strength of 116 MPa, a warpage of 1.2%, and a notched impact strength of 93 J / m. It is evident that the synergistic combination of the above components results in a carbon fiber reinforced polyamide composite material that balances the high strength of carbon fibers with the low shrinkage and low warpage of hollow microspheres, making it suitable for precision robot structural components such as robotic arm supports, connecting flanges, and module shells.

[0072] Example 3: The polyamide resin was treated with polyamide resin, fluorite, and nano-titanium dioxide. Examples 4-5: No fluorite or nano-titanium dioxide was added during the polyamide resin treatment. Table 1 shows that the tensile strength, warpage, and notched impact strength of Example 3 were significantly better than those of Example 1. The corresponding test results of Examples 4-5 were significantly worse than those of Example 3, but better than those of Examples 1-2. This indicates that fluorite possesses excellent solid lubrication properties; embedding it within the PA matrix can reduce the coefficient of friction in structural components, reduce wear and noise in robot moving parts, and improve overall performance such as wear resistance. Nano-titanium dioxide inhibits molecular chain aging of PA under long-term light exposure and ultraviolet disinfection of equipment, improving the long-term dimensional stability of exposed structural components of the robot.

[0073] Example 6: Carbon fiber was treated with talc and epoxy resin emulsion. Examples 7-8: Carbon fiber was treated without talc or epoxy resin emulsion. Table 1 shows that the tensile strength, warpage, and notched impact strength of Example 6 were significantly better than those of Example 3. The corresponding test results of Examples 7-8 were significantly worse than those of Example 6, but better than those of Example 3. This indicates that the epoxy resin emulsion, ensuring uniform impregnation composition, is incorporated into the epoxy coating after curing, weakening the brittleness of the pure epoxy film, buffering interfacial thermal stress and residual molding stress between the carbon fiber and the resin matrix, and suppressing warpage deformation of the product at the interfacial level. Simultaneously, it improves the wettability of the carbon fiber, allowing the coating liquid to penetrate into the fiber bundle, thus improving overall mechanical and other properties.

[0074] Example 9: Hollow glass microspheres were treated with graphene and silane coupling agent KH-550. Examples 10-11: Hollow glass microspheres were treated without graphene and silane coupling agent KH-550, respectively. Table 1 shows that the tensile strength, warpage, and notched impact strength of Example 9 were significantly better than those of Example 6. The corresponding test results of Examples 10-11 were significantly worse than those of Example 9, but better than those of Example 6. This indicates that the coated sheet graphene can construct a microscopic reinforcing network around the microspheres, offsetting the mechanical attenuation caused by the hollow structure, achieving a balance between low warpage, lightweight design, and structural strength, making it suitable for robot load-bearing structural components. The silane coupling agent KH-550 eliminates interfacial gaps and debonding defects between the inorganic microspheres and the organic resin, improving the overall performance of the system.

[0075] Comparative Example 1, without the addition of hollow glass microspheres, shows, as can be seen from Table 1, that the tensile strength, warpage, and notched impact strength of Comparative Example 1 are significantly worse than those of Examples 1-2. This indicates that hollow glass microspheres can significantly reduce material density, and their isotropic spherical structure helps reduce anisotropic shrinkage during molding, thereby suppressing warpage, improving dimensional stability, reducing creep after molding, minimizing dimensional deviation under long-term robot load, and improving overall mechanical properties.

[0076] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A low-warpage carbon fiber reinforced polyamide composite material for robot structural components, characterized in that, By weight, it includes the following raw materials: 60-70 parts polyamide resin, 20-30 parts carbon fiber, 0.6-0.9 parts silane coupling agent, 10-12 parts hollow glass microspheres, 2-5 parts polyethylene grafted maleic anhydride, and 0.5-0.8 parts antioxidant 1010.

2. The low-warpage carbon fiber reinforced polyamide composite material for robot structural components according to claim 1, characterized in that, The polyamide resin is treated with fluorite and nano-titanium dioxide.

3. The low-warpage carbon fiber reinforced polyamide composite material for robot structural components according to claim 1, characterized in that, The carbon fiber is treated with talc and epoxy resin emulsion.

4. The low-warpage carbon fiber reinforced polyamide composite material for robot structural components according to claim 3, characterized in that, Epoxy resin emulsion was mixed with dried talc powder, deionized water was added, and the mixture was stirred evenly to obtain a mixture. Short carbon fibers were immersed in the mixture, centrifuged, spread out and dried to obtain treated carbon fibers.

5. The low-warpage carbon fiber reinforced polyamide composite material for robot structural components according to claim 1, characterized in that, The hollow glass microspheres are treated with graphene and silane coupling agent KH-550.

6. The low-warpage carbon fiber reinforced polyamide composite material for robot structural components according to claim 5, characterized in that, Graphene was dispersed in a mixture of ethanol / deionized water, and silane coupling agent KH-550 was added. The mixture was stirred for 15-20 minutes to obtain the final mixture. Hollow glass microspheres were immersed in a mixed solution, centrifuged, and dried to obtain pretreated hollow glass microspheres.

7. The method for preparing a low-warpage carbon fiber reinforced polyamide composite material for robot structural components according to claim 1, characterized in that, Includes the following steps: Polyamide resin, silane coupling agent, hollow glass microspheres, polyethylene grafted maleic anhydride, and antioxidant 1010 are mixed evenly to obtain a mixed raw material. The above mixed raw material and carbon fiber are placed in the main feed port and side feed port of a twin-screw extruder, respectively, and then melt-extruded and granulated to obtain a low-warpage carbon fiber reinforced polyamide composite material for robot structural parts.

8. The low-warpage carbon fiber reinforced polyamide composite material for robot structural components according to claim 7, characterized in that, Twin-screw extruder settings: Zone 1 temperature 240-250℃, Zone 2 temperature 250-260℃, Zone 3 temperature 250-260℃, Zone 4 temperature 260-270℃, Zone 5 temperature 270-280℃, Zone 6 temperature 260-270℃, Zone 7 temperature 250-260℃, screw speed 320-330 rpm / min.